REGULASI EMOSI REMAJA GENERASI Z: PROBLEMATIKA DAN SRTATEGI BIMBINGAN KONSELING BERBASIS PENDIDIKAN AGAMA ISLAM (PAI) - Ahmad Makhasin Ma’arif; Baihaqi; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Emotion regulation is a crucial skill for adolescents to manage emotions adaptively while navigating various developmental demands. However, many adolescents struggle to regulate their emotions due to factors such as alexithymia, the use of maladaptive regulation strategies, unsupportive parenting styles, and pressures from social environments and digital media. These conditions can increase the risk of mental health issues—ranging from anxiety and depression to the emergence of risky behaviors. This article aims to examine the challenges of emotion regulation among adolescents, identify the influencing internal and external factors, and analyze the role of guidance and counseling—specifically that based on Islamic Religious Education (PAI)—as a strategy for fostering healthy emotion regulation skills. The study employs a literature review method, analyzing relevant books and scholarly articles. The findings indicate that adolescent emotion regulation is influenced by external factors (family, school, peers, and social media) and internal factors (age, gender, cognitive development, religiosity, and educational level). Guidance and counseling services that adopt preventive and developmental approaches—integrated with PAI-based strategies such as instilling values of patience (sabr), gratitude (shukr), and reliance on God (tawakkul); spiritual practices like prayer and dhikr; and Islamic counseling emphasizing counsel and role modeling—have proven effective in strengthening psychological resilience and enhancing students' emotion regulation capabilities. Successful implementation of these strategies requires sustained collaboration among guidance and counseling teachers, Islamic Religious Education teachers, and parents to support the emotional and spiritual development of adolescents.